KULTUR JARINGAN JERUK KASTURI (Citrus microcarpa) DENGAN MENGGUNAKAN HORMON KINETIN DAN NAFTALEN ACETYL ACID (NAA) SEBAGAI PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS VIRTUAL LABORATORY PADA KONSEP BIOTEKNOLOGI MODERN DI SMA - Suci Agustiani Agustiani; Imam Mahadi Mahadi; Wan Syafi’i Syafi'i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aimed to determine the effect of Kinetin and NAA on the growth of explants Musk lime (Citrus microcarpa) and to design learning resource for student work sheet based virtual laboratory. This research was conducted at the Laboratory of Biology Education University of Riau and Laboratory Biotechnology of Riau Islamic University from April-Mei 2015, using a completely randomized design of 4 x 4 factorial with three replications. The first factor (K) is the Kinetin consists of 4 level: 0 ppm, 1 ppm, 3 ppm, and 5 ppm. The second factor (A) is the NAA consist of 4 level: 0 ppm, 0,5 ppm, 1 ppm, and 2 ppm. Parameters measured were percentage grows, time of root rise, time of bud rise, the amount of buds, amount of roots, and lengt shoot. The data were analyzed using ANAVA and tested further by DMRT at 5% level. The data were analyzed using verification by lecturer for development student work sheet . The results of this research showed of Kinetin and NAA significantly affect the growth of explants Musk Lime. The percentage of explants grown 100% all treatments, except treatment K5A0, The earliest of root rise in treatment K0A0,5 HST, The earliest of bud rise in treatment K5A0 HST, Highest amount of buds in treatment K3A2 is 2.4 buds, Highest lengt of shoot in treatment K3A0 is 7.1 buds, and the amount of roots the best treatment of K0A0,5 is 8,1 roots. Results of reserach can be used as development student work sheet based on virtual laboratory  in modern biothecnology concept for class xii senior high school. Keywords: Kinetin, NAA, Student Work Sheet, Tissue Culture.